Psychological distress in patients awaiting heart transplantation - Zipfel, Stephan; Löwe, Bernd; Paschke, T.; Immel, Beate; Lange, Rüdiger; Zimmermann, Rainer Johannes; Herzog, Wolfgang; Bergmann, Günther (Journal of psychosomatic research, 1998)
Heart transplantation has become an established procedure for the treatment of terminal heart failure. However, due to a shortage of donor organs, the waiting period for a donor organ is increasing. Cross-sectional and retrospective studies have indicated that there is tremendous psychological distress during this waiting period. The aim of this study was to assess this phase systematically and longitudinally. At the beginning of their waiting period, 62 patients at the Heidelberg Transplantation Centre were examined with regard to their physical complaints, quality of life, and level of depression. Four months later the remaining 42 patients were re-examined. The sample showed a significant increase (p<0.001) in subjective physical symptoms and an impairment in social activities (p<0.05) and everyday life (p<0.05), and a significant increase in depression (p<0.001), despite the relatively short time period. These results show the necessity of supportive psychotherapy for patients undergoing heart transplantation.
Gesehen am 02.10.2025